Is the United States Supreme Court an undemocratic institution? An outsider’s perspective - Machaj, Łukasz (University of Wroclaw. Faculty of Law, Administration & Economics, 2011)
The United States Supreme Court has often been accused of engaging in judicial activism, of subverting legislatures’ will and of undermining the basic principles of the democratic system. This article maintains that such charges are generally unfounded. The author claims that the Supreme Court’s detractors ignore five fundamental issues. First, they misunderstand the very nature and basic rules of a constitutional democracy. Second, they tend to ignore the role played by constitutions in general and the American Constitution in particular in social reality, effectively forgetting the reasons for the latter’s hallowed place in the United States national psyche. Third, they ignore the presence of political factors (and even partisan calculations) in the process of appointments to the U.S. Supreme Court. Fourth, they misconceive the realities of the process of legal reasoning and of constitutional interpretation. Fifth, they underestimate or even fail to recognize the influence of public opinion on the basic trends of judicial decision-making.
Keywords: United States Supreme Court